Design, Synthesis and Evaluation of CNS Depressant Activity of 2-(Substituted Aryl)-Piperazine-3-Phenyl-4(3H)-Quinazolinone (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Anxiety is characterized by excessive fear that persists and interferes with a person's daily activities. In this study, a new class of 16 derivatives of 2-(Substituted Aryl)-piperazine-3-phenyl-4(3H)-quinazolinones were synthesized, and all of the derivatives were tested for their ability to reduce anxiety using the holeboard test and the elevated plus maize test, administered intraperitoneally to mice at doses of 10 mg/kg body weight. Test compounds 3-phenyl-2-(4-(3-methylphenyl) piperazin-1-yl)quinazolin-4(3H)-one (SD-05), 2-(4-(2-fluorophenyl) piperazin-1-yl)-3-phenylquinazolin-4(3H)-one (SD-06), 3-phenyl-2-(4-(4-methoxyphenyl) piperazin-1-yl)-quinazolin-4(3H)-one (SD-10) showed an increased number of head pocking (56 ± 3.5 to 70 ± 1) as compare to control group number of head pocking (27 ± 3) and increased duration of pocking (50 ± 12 ns) as compare to control group duration of pocking (25 ± 2) in hole board test and increased time spent in open arm (35.5 ± 1.5) and a number of entries in open arm (12.5 ± 0.50) as compare to control group. Test compounds SD-05, SD-06, SD-10 showed significant antianxiety activity.